History of contemporary self-image - Misbah Islam; Natalie Samynadin (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
This paper aims to describe how the development of the art of selfie photography in the world. This research is library research; the author seeks various reading materials that support the acquisition of data. The reading article is a book and research results published in libraries and online. This study shows that in history, selfies do not only talk about narcissism but have a strong cultural philosophy.